ChemInform Abstract: Iron(III)triflate as a Highly Efficient, Recyclable and Green Catalyst for the N‐Boc Protection of Amines. Issue 24 (2nd June 2014) - Feng, Chengliang; Chu, Ningning; Zhang, Shuguang; Cai, Jin; Chen, Junqing; Hu, Huayou; Ji, Min
Abstract Various aliphatic, aromatic, and heterocyclic amines as well as aminols are selectively protected as monocarbamates in excellent yields and short reaction times.